Meningkatkan Hasil Belajar IPA Melalui Model Problem-Based Learning (PBL) Pada Siswa Kelas V SDN 31 Mataram - Awaludin, Awaludin; Hidayati, Vivi Rachmatul; Purwani, Ketut (Journal of Science Instruction and Technology, 2024)
This research is motivated by the low science learning outcomes of fifth grade students at SDN 31 Mataram, especially on the Single Substance and Mixture material. This study aims to determine the improvement in learning outcomes through the application of the Problem Based Learning (PBL) model. This type of research uses Classroom Action Research (CAR) which involves four stages: planning, implementation, observation, and reflection. CAR was carried out in two cycles in fifth grade with a total of 16 students, consisting of 6 males and 10 females. The results of the study showed that the application of the PBL model can improve students' science learning outcomes on the Single Substance and Mixture material. The improvement in learning outcomes can be seen from the average value and the percentage of classical completion which is getting higher in each cycle. The average value of students in the initial condition (pre-cycle) was 70 with a classical completion of 40% (6 students achieved a score of ≥ 75). In Cycle I, the average value increased to 74 with a classical completion of 60% (10 students). In Cycle II, the average value reached 81 with classical completion of 80% (13 students). This shows that the PBL model is effective in improving student learning outcomes.